Evaluating the Diagnostic Value of a Combined Indicator of Vitamin B12 Status (cB12) Throughout Pregnancy - Dib, Marie-Joe; Gumban-Marasigan, Maria; Yoxall, Rozzie; Andrew, Toby; Harrington, Dominic J.; Sobczyńska-Malefora, Agata; Ahmadi, Kourosh R. (Frontiers in Nutrition, 2022)
Inadequate provision of vitamin B12 during pregnancy is associated with a number of adverse maternal and foetal outcomes. We set out to (1) suggest pregnancy-specific reference ranges for a range of biomarkers of vitamin B12; (2) assess the temporal behaviours of these markers over the course of pregnancy; and (3) test whether any biomarkers, including the genetic marker HIBCH rs291466 strongly associated with MMA measured early in pregnancy could reliably and significantly predict future B12 status within a healthy UK population of pregnant women. We used existing biobank samples from the placebo arm of the UK Selenium in PRegnancy Intervention (SPRINT) study, to generate biochemical data for serum folate, B12, holotranscobalamin (HoloTC), total homocysteine (tHcy), and MMA, calculate cB12, and genotyped the polymorphism rs291466 in gene HIBCH on a total of n=114 women across trimesters 1-3 of their pregnancy. We performed a series of exploratory cross-sectional and longitudinal analyses to investigate levels at each trimester, suggest references ranges, evaluate changes and correlations between the B12 biomarkers, and assess the predictive capabilities of each biomarker from 12-weeks to 35-weeks of gestation. Significant changes in all vitamin B12 biomarker values were observed over the three trimesters (P<0.05). Our study shows that cB12 values were largely constant and stable throughout trimester 1 (T1) and T2 (i.e. up to week 20), but declined significantly in T3 (-66% | P<0.001). We identified pregnancy and trimester-specific reference ranges for each biomarker at each trimester, using 5th or 95th percentile cut-offs. Our multivariate analyses indicated that none of the biomarkers could reliably and accurately predict any other biomarkers than themselves later in pregnancy although HoloTC stood out as the most robust predictor. Most notably, cB12 did not significantly predict itself between trimesters. Finally, we show that the HIBCH variant has little predictive power for MMA or cB12 as it does not explain the significant increase in MMA concentrations nor the decline of cB12 throughout pregnancy. Trimester-specific reference ranges for biomarkers of vitamin B12 in normal pregnancy are suggested. However, these biomarkers have limited predictive value in identifying mothers at elevated risk of vitamin B12 insufficiency/deficiency during pregnancy.